(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2026)
Background: Endocrine disorders make up a significant and expanding portion of non-communicable diseases in Bangladesh; there is still a dearth of thorough outpatient data from the country. Objective: This study aimed to describe the spectrum of endocrine disorders encountered in specialized endocrine outpatient departments (OPDs) across government and private hospitals in Bangladesh and to classify these disorders using the World Health Organization (WHO) ICD-11 coding system. Methods: We conducted a multicenter cross-sectional study using retrospective data from the endocrinology OPDs of three healthcare settings (government, private, and diagnostic consultation centers) in urban and semi-urban Bangladesh. Consecutive patients attending OPDs between September 2022 and December 2025 were included. Demographic and clinical data were extracted from hospital registries and electronic medical records. Endocrine disorders were classified according to the WHO ICD-11 framework. Results: Among 17,069 OPD attendees, 16,531 (96.84%) endocrine diagnoses were recorded. The mean age was 40.3±15.2 years, with female predominance 11792 (71.3%). Endocrine pancreatic disorders were most prevalent, 8522 (43.9%), largely dominated by type 2 diabetes mellitus 7958 (93.4%). Thyroid disorders 5889 (30.3%), obesity/metabolic syndrome 2312 (11.9%), and reproductive endocrine disorders 1470 (7.5%) were the next prevalent disorders. Overt hypothyroidism and polycystic ovary syndrome were the most frequent thyroid and reproductive disorders, respectively. Diabetes predominated in the 40–60-year age group, whereas thyroid disorders were more common among younger adults and females. Conclusion: This large multicenter OPD-based study demonstrates a substantial burden of diabetes and thyroid disorders in Bangladesh, with marked female predominance and significant reproductive endocrine morbidity. The findings underscore the need for integrated endocrine care, targeted screening strategies, and strengthened public health interventions to address the rising burden of endocrine diseases in Bangladesh. [J Assoc Clin Endocrinol Diabetol Bangladesh, January 2026; 5(1): 35-44]